Content Analysis of Undergraduate Research in Business Management at Cavite State University, Philippines - PAITON, JANICE; CUENO, GENER; FELICIANO, PRINCESS; MELO, TANIA MARIE; RUPIDO, SHERRIE RHOSE (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study examined the research trends, methodological characteristics, and thematic alignment of undergraduate research outputs in Business Management at Cavite State University, Philippines, covering the period from 2012 to 2018. Using a descriptive research design and content analysis approach, the study analyzed 492 approved undergraduate theses archived in the university library. The analysis focused on research themes, methodological approaches, alignment with the research agenda of the college, significant findings, recommendations, and the extent of research dissemination. Results revealed that undergraduate research outputs were predominantly descriptive and concentrated on selected thematic areas such as financial management, consumer behavior, employee rewards and maintenance, supply chain management, and economic development. While most studies aligned with the institutional research agenda—particularly in community development, institutional performance, and organizational capability—several priority areas received limited research attention. The findings also indicated heavy reliance on survey-based methods and non-probability sampling techniques, with minimal use of advanced or mixed research designs. Moreover, dissemination of undergraduate research outputs was notably limited, as few theses were presented in academic forums and none were published. The study contributes to knowledge by providing a systematic, longitudinal assessment of undergraduate research patterns across multiple business specializations. The findings highlight key gaps in research focus, methodology, and dissemination that have implications for curriculum development, research mentoring, and institutional research policy. Overall, the study underscores the need to strengthen undergraduate research training and support mechanisms to improve research quality, relevance, and scholarly visibility.